New family of multilength multi-wavelength reed-solomon code of OCDMA system - ZHOU Xiu-li 1; MA Jun-xian2; HU Yu1 (Tongxin xuebao)
A new class of multilength, constant-weight two-dimensional multi-wavelength reed-solomon （2D MW RS） code with large capacity and good correlation properties was constructed. The performance of these new MW RS codes with two kinds of lengths in an OCDMA network was analyzed. The result shows that media with the shorter code words performs much better than the media with longer codeword, and OCDMA system with these new multilength MW RS codes performs well. These features allow large capacity multimedia transmission with different bit-rate and qual- ity-of-service requirements accommodated simultaneously in OCDMA network system.